Editors' Choice—State of Charge Dependent Resistance Build-Up in Li- and Mn-Rich Layered Oxides during Lithium Extraction and Insertion. Issue 6 (16th April 2019) - Teufl, Tobias; Pritzl, Daniel; Solchenbach, Sophie; Gasteiger, Hubert A.; Mendez, Manuel A.
Abstract : Lithium- and manganese-rich layered oxide-based cathode active materials (often referred to as HE-NCM) exhibit high reversible specific capacity (≈250 mAh/g) and could improve future lithium-ion batteries in terms of energy density and safety, while offering lower cost. Unfortunately, drawbacks such as voltage-fading, hysteresis, and increasing cathode impedance over charge/discharge cycling have so far hindered its commercialization. In this study, we examine the reasons and the implications of the high resistance build-up of this material in graphite//HE-NCM full-cells. Impedances/resistance were obtained either by electrochemical impedance spectroscopy (EIS) with a micro-reference electrode or by current pulse measurements (so-called direct-current internal-resistance (DCIR) measurements). These data show that the so-called activation of the material above 4.5 V vs. Li + /Li leads to an asymmetric high charge-transfer impedance at low state-of-charge (SOC) between charge and discharge, manifested as an anomalous cell resistance hysteresis which increases over cycling and with increasing upper cutoff potentials. These findings are rationalized by reversible transition-metal migration phenomena.